The Norske Nook Book of Pies and Other Recipes - Bechard, Jerry; Borton-Parker, Cindee (Book collections on Project MUSE., 2015)
"The Norske Nook's mile-high meringue and dairy-state deliciousness attracts foodies, celebrities, and tourists from around the world, as well as the locals. Founded as a small-town cafe in 1973, the Norske Nook is now a foursome of revered pie shrines in Osseo, Rice Lake, Eau Claire, and Hayward, Wisconsin. The Nook's international fame grew from a tradition of Midwest home making, informed by Scandinavian roots and enriched by the luscious ripe fruit and sumptuous sour creams and cream cheeses of America's dairyland." -- Dust jacket.